2017
DOI: 10.1039/c6pp00266h
|View full text |Cite
|
Sign up to set email alerts
|

The role of UVR and vitamin D on T cells and inflammatory bowel disease

Abstract: Vitamin D deficiency is associated with the development of inflammatory bowel disease (IBD). In experimental IBD the targets of vitamin D that result in protection from IBD include gut epithelial cells, innate immune cells, T cells and the microbiota. Ultraviolet radiation (UVR) induces production of vitamin D in the skin and suppresses T cell responses in the host. There is limited data demonstrating an effect of UVR on experimental IBD but the mechanisms of UVR suppression in IBD have not been defined. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Through active intestinal signaling, which has immunomodulatory and immunosuppressive effects on inflammatory and inhibitory markers of IBD, VitD interferes with the immune response to bacterial activity, antigen presentation and adaptive and innate immune regulation. Therefore, VitD may affect the incidence and progression of UC and CD [1012]. While attempting to rule out VitD deficiency in patients with IBD due to reduced physical activity, sunlight exposure, malnutrition, inadequate dietary intake of VitD, or lower bioavailability, some studies [3, 13, 14] have found that VitD deficiency is also common in newly diagnosed IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Through active intestinal signaling, which has immunomodulatory and immunosuppressive effects on inflammatory and inhibitory markers of IBD, VitD interferes with the immune response to bacterial activity, antigen presentation and adaptive and innate immune regulation. Therefore, VitD may affect the incidence and progression of UC and CD [1012]. While attempting to rule out VitD deficiency in patients with IBD due to reduced physical activity, sunlight exposure, malnutrition, inadequate dietary intake of VitD, or lower bioavailability, some studies [3, 13, 14] have found that VitD deficiency is also common in newly diagnosed IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggested a relationship between VitD with the incidence of autoimmune diseases ( 14 , 15 ). Additionally, VitD supplementation prevents both the initiation and progression of experimental autoimmune encephalomyelitis and experimental models of multiple sclerosis and rheumatoid arthritis ( 16 , 17 ). Recently, VitD deficiency or insufficiency was associated with respiratory disease in children, as revealed by accumulating epidemiologic evidence ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that VD inhibits T cell proliferation and suppresses IFN-γ and IL-17 production by T cells. Conversely, VD is known to increase IL-4 production from T cells [22]. In CD and UC patients, 25(OH)D 3 serum levels are lower than in healthy controls [23].…”
Section: Introductionmentioning
confidence: 99%